Pollen Spectrum and Bee Flora Diversity in Northern Balochistan, Pakistan: A Melissopalynological Study - Sherani, Afsana; Bibi, Tahira; Irfan, Shazia; Shaukat, Kanval; Sajjad, Naheed; Ali Ahmed, Hina; Jamil, Nelofer; Makai, Gul; Mengal, Samina; Tareen, Niaz Muhammad (Journal of Neonatal Surgery, 2025)
Melissopalynology, the study of pollen grains in honey, is a valuable tool for identifying floral resources exploited by bees and for determining the botanical and geographical origin of honey. This study aimed to document the diversity of bee forage plants in Northern Balochistan, Pakistan, and to highlight the region’s potential for sustainable apiculture. Five fresh honey samples were collected from local beekeepers in Ziarat, Loralai, Khanozai, Quetta, and Muslimbagh, along with representative plant specimens from the surrounding habitats. Pollen analysis was performed using the acetolysis method, and slides were prepared from floral anthers and honey samples to identify pollen taxa. All honey samples were classified as multifloral. A total of 30 pollen types representing multiple plant families were identified. The dominant taxa included Sonchus oleraceus, Peganum harmala, Helianthus annuus, Malus pumila, and Punica granatum. The family Asteraceae was the most prominent, being consistently present across all honey samples. Seasonal variation in pollen diversity was also observed, with higher representation of taxa during peak flowering periods. The pollen spectrum corresponded closely with the surrounding vegetation, confirming the reliability of melissopalynological analysis. The results demonstrate that the honey of Northern Balochistan is of multifloral origin and reflects the rich floral diversity of the region. These findings highlight the ecological significance of native plant species in sustaining honeybee populations and underscore the potential for developing apiculture as a sustainable livelihood. Conservation of key forage plants is recommended to support both ecological balance and local beekeeping practices